[BP.03.03] CARDIOVASCULAR RISK AND HYPERTENSION CONTROL IN ITALY. DATA FROM THE 2015 WORLD HYPERTENSION DAY. (September 2017) - Torlasco, C.; Faini, A.; Makil, E.; Ferri, C.; Borghi, C.; Schillaci, G.; Veglio, F.; Desideri, G.; Rosei, E. Agabiti; Ghiadoni, L.; Pauletto, P.; Pontremoli, R.; et al.
Abstract : Objective: Cardiovascular diseases (CVD) are the first cause of death and disability in western countries. Despite therapeutic advances, their prevalence is constantly increasing. Detailed assessment of modifiable CV risk factors could improve CVD prevention and management. Aim of this study is to assess CV risk and BP control in a sample of the Italian population. Figure. No caption available. Design and method: To assess CV risk and hypertension control in a sample of the Italian population, individuals participating to the 2015 "World Hypertension Day" were interviewed in 62 sites all over Italy. Blood pressure was measured with a validated auscultatory or oscillometric device and information on demography and prevalence of CVD risk factors was collected by an anonymous questionnaire. An ad-hoc modified version of the Systematic COronary Risk Evaluation (SCORE) system was then applied. Results: 8657 recruited individuals (43%women, aged 56.68 ± 16 years) were subdivided into 3 age groups (40–49y, 50–59y, 60–69y) for analysis. CV risk was low in 62.4%, 18.0% and 0%; moderate in 26.0%, 66.0% and 62.5%; high/very high in 11.6%, 16% and 37.4%, respectively. Smoking was mainly responsible for increased CV risk among those aged 40–49y (26%smokers), while hypertension was the main factor in the whole sample and in subjects over 50y (36% and 42% respectively). Overall, BP control was unsatisfactory in 36% of individuals (28%, 48% and 31% of those who declared to be normotensive, hypertensive on treatment or unaware of their BP condition, respectively). Conclusions: In this sample of the Italian population CV risk was alarmingly high, irrespectively of age, mostly due to presence of modifiable risk factors, including hypertension, which should thus be better addressed, especially in the youngsters.